La gestión de calidad y la satisfacción del cliente en la Empresa Mobiliaria BM en el Cantón Saquisilí. - Bravo Chancusig, Erick Fernando (2025)
The purpose of this research was to determine how quality management affects customer satisfaction in the Mobiliaria BM company, located in the Saquisilí canton, a problem was identified related to the absence of adequate quality management in internal processes, which is reflected in a low level of customer satisfaction regarding the products and services offered by the company. The study population consisted of 21 regular customers, to whom were applied a structured survey to gather direct information about their perception, while internally an interview was conducted with the owner-manager, allowing for a deeper understanding of the organizational context. Thanks to the Data collection it was possible to identify several weaknesses, including lack of planning, inefficient use of resources, deficiencies in after-sales service, and delays in delivery times— factors that reflect ineffective quality management. Through statistical analysis and hypothesis testing, it was confirmed that there is a significant relationship between quality management and customer satisfaction, demonstrating the urgent need to improve internal processes. Based on the findings, a quality management model was proposed, which includes the standardization of production processes, the implementation of an order control system, continuous staff training, and mechanisms for monitoring customer satisfaction, with the aim of improving organizational performance and strengthening the relationship with customers.